Infernal Heavens: Narratives of Africa. From Joseph Conrad's Heart of Darkness to Abdulrazak Gurnah's Paradise - Botescu Sireteanu, Ileana (University of Bucharest, 2024)
Situated at the intersection of literary studies and cultural studies, the present article looks at how fictional representations of Africa have evolved over the past century, from Conrad's canonical Heart of Darkness, which has unjustly become the landmark of colonial biased narratives of Africa despite the author's declared disengagement with his protagonists' perspectives, to Abdulrazak Gurnah's recent reverse rewriting of Marlow's journey, this time from the heart of darkness outward. Dwelling on the spatial metaphors of Heaven and Hell, this study argues that the two works under scrutiny put forward two essentially dichotomic representations of the same place, the African continent, which are largely dependent on the cultural environment and on cultural constraints. Whereas Conrad's infernal depiction of Africa relies mostly on Eurocentric stereotypes and on a personal experience whose horror mostly stemmed from a cultural shock produced by experiencing difference as evil, Gurnah's more complex and authentic depiction is a result of telling the story from within, as an insider, and reflecting on difference as productive diversity. In this respect, this study brings into discussion Ranjan Ghosh's recent dialogue with J. Hillis Miller on Literature and Globalization (2016) to argue that a transnational, transcultural and transdisciplinary approach to the narrative text would actually result in bridging the gap of classical binary difference and would emphasize the immanence of the literary text. Thus, Gurnah's Paradise reconstructs pre-WWI Africa from within, as a sum of lost Paradises which are by no means of Western extraction, while Conrad's canonical Inferno echoes the fears of an empire.
Keywords: Africa; identity; Joseph Conrad; Abdulrazak Gurnah; time; space; colonialism; globalization.